2022
DOI: 10.1177/19389655221102388
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Customer Reviews for Local and Chain Restaurants: Multilevel Approach to Google Reviews Data

Abstract: Online reviews influence customer decisions and present publicly available data to investigate differences between customer evaluations for local and chain businesses. We conduct a text analysis on a sample of 80,728 online customer reviews of quick-service restaurants to examine how the impact of dining experience attributes on customer evaluation differs between the two restaurant types. Estimation of multilevel multinomial models reveals that customer reviews for local restaurants have less polarized sentim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Ambience and service, the feeling of being at home away from home, are quintessential features of this type of restaurant, and restaurant reviewers often mention them, as presented in this research. On the other hand, the standardization of taste at diners may contribute to less focus on food attributes as highlighted in an earlier study on fast food chains (Yalcinkaya & Just, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambience and service, the feeling of being at home away from home, are quintessential features of this type of restaurant, and restaurant reviewers often mention them, as presented in this research. On the other hand, the standardization of taste at diners may contribute to less focus on food attributes as highlighted in an earlier study on fast food chains (Yalcinkaya & Just, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A study compares customer reviews for local and chain restaurants and finds that while food quality is crucial in local restaurants, service quality is the main factor in chain restaurants. The study's results indicate that food attributes have a less significant impact on customer satisfaction levels in chain restaurants, perhaps due to the standardization of taste in fast‐food chains (Yalcinkaya & Just, 2023).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Furthermore, the study compared customer reviews between local restaurants and chain restaurants by using a multilevel approach to examine data from Google reviews [11]. The study revealed that in the case of local restaurants, food quality holds a more significant impact in determining customer satisfaction.…”
Section: Dimensions Of Food Qualitymentioning
confidence: 99%
“…Moving on to service quality, a critical determinant of customer satisfaction in Islamic banks, a wealth of research by Ahmed et al (2020), Biswas et al (2023), Chatterjee et al (2023), Jasin and Firmansyah (2023), Kim et al (2023), Mir et al (2023), Ong et al (2023), and Yalcinkaya and Just (2023) accentuates its paramount importance. Post-merger, service quality in Islamic banks typically results in heightened customer satisfaction, with good service quality positively impacting customer loyalty, while service failures can lead to switching behaviour (Zhao et al, 2022(Zhao et al, , 2023.…”
Section: Literature Reviewmentioning
confidence: 99%